Uncovering the emotional exhaustion of PTN-BH lecturers: The impact of workload, interpersonal relationships, and change-related communication - I'anah, Noor; Sawitri, Dian Ratna; Purba, Debora Eflina; Riantoputra, Corina D. (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: Emotional fatigue is a growing concern among academics, with over 50% of lecturers in Indonesia experiencing emotional exhaustion. Perguruan Tinggi Negeri Berbadan Hukum (PTN-BH) face high autonomy along with heavy tridarma responsibilities and performance pressures, often without adequate financial or emotional support. Research focusing specifically on PTN-BH lecturers remains limited.Purpose: To examine work-related stressors—workload, interpersonal relationships, and change-related communication—that contribute to emotional exhaustion among PTN-BH lecturers, using the Job Demands Resources theory (55.9% female; Mage = 42.54; SDage = 10.6).Method: A cross-sectional survey was conducted involving 306 PTN-BH lecturers in Indonesia (55.9% female; Mage = 42.54; SDage = 10.6). Data were analyzed using moderated multiple regression in IBM SPSS version 25.Findings: Workload and change-related communication showed significant effects on emotional exhaustion. In contrast, interpersonal relationships and the moderating role of self-leadership were not statistically significant.Implication: Addressing excessive workload and improving communication during organizational changes are essential to reduce emotional exhaustion and promote well-being among PTN-BH lecturers.